(Poly)phenol‐Rich Diets in the Management of Endothelial Dysfunction in Diabetes Mellitus: Biological Properties in Cultured Endothelial Cells. Issue 15 (20th June 2021) - Rocha, Sara; Oskolkova, Olga; de Freitas, Victor; Reis, Ana
Abstract: Processed and ready‐to‐eat foods become routinely consumed resulting in a sharp rise of sugar intake in people's daily diets. The inclusion of fresh fruits and vegetables rich in (poly)phenols has been encouraged by the World Health Organization (WHO) as part of the daily choices to ameliorate endothelial dysfunction and ease the socio‐economic burden of diabetes. Research in Food, Nutrition, and Cell Metabolism areas is revealing that the health benefits of (poly)phenol‐rich foods go beyond their antioxidant properties and are in fact key modulators of redox and glycaemia status, and inflammatory response contributing to improved endothelial function and vascular health in diabetes. Other beneficial aspects include appetite modulation, regulation of hydrolytic enzymes involved in sugar and lipid metabolism, and mediation of cell–cell aggregation events. This work overviews the current knowledge on the biological properties of ingested (poly)phenols in cultured endothelial cells with emphasis on the circulating (poly)phenols, providing support to (poly)phenol‐rich diets as alternatives to drug‐based therapies in the prevention, treatment, and management of diabetes. A critical evaluation on the caveats and challenges involve in current experimental cell‐based designs and approaches adopted is also discussed. Abstract : WHO recommends (poly)phenol‐rich diets to manage diabetes complications. Dietary (poly)phenols have high antioxidant capacity and modulate appetite, glucose uptake, and inflammatory response. Metabolization alters (poly)phenol structure and chemical stability in neutral media. (Poly)phenol metabolites have poor antioxidant capacity but still modulate redox and glycaemia status, inflammatory response, and aggregation events. The occurrence of metabotypes will impact endothelial research in diabetes.